Tinjauan Hukum terhadap Penyelesaian Sengketa Perdata melalui Mediasi di Pengadilan Negeri Denpasar - Arnoldus Yansen Seran; Nurianto Rachmad Soepadmo; Kadek Fredi Andrika Adantara (Jurnal Riset Rumpun Ilmu Sosial, Politik dan Humaniora, 2026)
Mediation, as one of the alternative dispute resolution (ADR) mechanisms in civil cases, aims to provide efficient, timely, and non-confrontational solutions for disputing parties. Within the Indonesian legal system, mediation has been formally regulated through the Supreme Court Regulation (PERMA) No. 1 of 2016 concerning Mediation Procedures in Court. This study seeks to examine the implementation of civil dispute resolution through mediation from a legal perspective while also assessing its empirical effectiveness in district courts. The research employs an empirical juridical approach, with data collected through in-depth interviews with mediator judges, advocates, and disputing parties who have participated in the mediation process, supported by documentation studies of civil case decisions resolved through mediation. The findings reveal that, normatively, mediation has a sufficiently strong legal foundation as an alternative method of dispute resolution. However, its practical effectiveness remains constrained by several challenges, such as the limited understanding and legal awareness of disputing parties, time constraints faced by mediator judges, and the absence of an optimal supervisory mechanism for monitoring mediation practices. These factors contribute to the relatively low success rate of mediation in practice. Therefore, improvements are required in the implementation of regulations, the establishment of more effective monitoring systems, and the enhancement of human resource capacity, particularly mediator competence. Strengthening these aspects is expected to enable mediation to function more effectively as a fair, efficient, and accessible mechanism for resolving civil disputes in Indonesia.